Pengaruh Metode Kauny Quantum Memory Dalam Meningkatkan Hafalan Al-Qur’an Siswa Pada Program Tahfidz Di Mts Muhammadiyah Purwokerto - Abror, Farhan; Khoirul Azis, Donny (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The background of this study is the low ability of students to memorize the Qur'an. To answer this problem, the kauny quantum memory method is used as an effort to improve the quality of student memorization. The purpose of this study was to determine how much influence the kauny quantum memory method has on the ability to memorize the Qur'an of class VII students at MTs Muhammadiyah Purwokerto. This study is included in the type of quantitative research with a quasi-experimental approach, because there is a certain treatment given to the experimental group, and the design used is the Pretest-Posttest Control Group Design. Data were obtained through pretest and posttest administration, then analyzed using the N-Gain calculation. The results of the analysis showed that the average N-Gain value of the experimental class was 0.61 (moderate category), while the control class had an average of 0.46 (moderate category). However, the increase in memorization in the experimental class was higher than the control class. Based on the t-test on the posttest results, a significance value of 0.003 (<0.05) was obtained, which indicated a significant difference in the ability to memorize the Qur'an between the two classes. From these results, it can be concluded that the application of the kauny quantum memory method has an influence on improving students' Al-Qur'an memorization abilities in the tahfidz program at MTs Muhammadiyah Purwokerto.